First and forever - Painter, Lynn (Berkley Romance, 2026)
"A football star and a diehard fan entangled in a PR stunt-that only one side knows is fake-might be the right play in this new romantic comedy by #1 New York Times bestselling author Lynn Painter. Duffy Distefano loves three things: her dad, the family cat, and Minneapolis Coyotes football. So when she gets booed out of a game and becomes the internet's villain, she is distraught-and disgruntled. All she did was shove Coyote Carl away when he made a move on her, but everyone else just saw a woman attacking their team's beloved mascot. Eager to clear the air, Duffy agrees to an interview on a hit morning show. She doesn't expect a co-guest to join her-especially not the Coyotes' star tight end. When MVP Connor Cunningham gets tasked with damage control to help his team out of their PR nightmare, he thought that meant saying a few words on the team's behalf. Instead, he finds himself in a highly amusing verbal sparring match with a recently wronged fan on live TV. Duffy pelts him with fiery jabs but is also clearly diehard about the Coyotes-color him intrigued...and attracted. The interview instantly goes viral, and the public is obsessed with them. A strong push from the Coyotes' PR team to ride the wave results in Connor asking Duffy out. Despite his distaste for PR stunts, he's surprised to discover that being with Duffy is much easier than he thought, and somehow it doesn't feel fake to him. Harboring this secret can only blow up, but all he knows is that if he messes things up with Duffy, it'll be the greatest fumble of his life"-- Provided by publisher.